NOTE ON A SAND CULTURE TECHNIQUE FOR GROWING SLASH PINE (Pinus elliottii) - Malavolta, E.; Haag, H. P.; Sarruge, J. R. (REVISTA DE AGRICULTURA, 2016)
NOTE ON A SAND CULTURE TECHNIQUE FOR GROWING SLASH PINE (Pinus elliottii)